Effects of isopropanol-butanol-ethanol (IBE) on combustion characteristics of a RCCI engine fueled by biodiesel fuel - Okcu, Mutlu; Varol, Yasin; Altun, Sehmus; Firat, Mujdat (Elsevier, 2021)
The reactivity controlled compression ignition (RCCI) strategy using fuels with different reactivity's has attracted attention due to its high thermal efficiency as well as very low NOx and PM emissions in comparison to conventional combustion. As previous studies have shown that the type and amount of low reactivity fuel have a significant contribution to the in-cylinder reactivity, thus RCCI combustion, in this study, Iso-Propanol-Butanol-Ethanol (IBE), which has comparable characteristics to n-butanol and ethanol, is employed as low reactivity fuel (LRF) in a RCCI engine fueled by petroleum based EN590 fuel and commercial biodiesel. The IBE mixture was in volumetric ratios of 3:6:1 as in the fermentation process of butanol, that is to say; 30% Iso-Propanol, 60% Butanol and 10% Ethanol. In each experimental condition, keeping the total energy of the fuel supplied to the engine in conventional combustion mode for each cycle as constant, the premixed ratio (Rp) in case RCCI combustion was applied as 0%, 15%, 30%, 45% and 60% (the amount of LRF in energy basis) over this energy amount. The effect of premixed ratio of IBE on combustion characteristics were investigated in a single-cylinder RCCI engine under different loads with using both petroleum diesel and biodiesel as high-reactivity fuels (HRF), respectively. According to experimental results, a higher in-cylinder pressure was measured by using diesel in both conventional and RCCI mode compared to the use of biodiesel. Considering the peak in-cylinder pressure and rate of heat release, the premixed ratio (Rp) of up to 45% was found as optimum for all loads while it was up to 30%Rp for the NOx emissions. In addition, the biodiesel-fueled RCCI engine produced the lowest smoke opacity in all loads and it gradually decreased by up to 97% with the application of the RCCI strategy. Furthermore, the results showed that a simultaneous reduction in NOx and smoke opacity could be obtained under 60% load and up to 30% Rp with a marginal increase in unburned HC emissions.
Keywords: RCCI; Combustion; IBE; Biodiesel; Emissions